Penyuluhan Gemar Makan Ikan dan Demonstrasi Produk Hasil Perikanan di Desa Muntai Barat - Sirait, Putriana Sari; Zebua, Putra Sutrisman; Hutabarat, Putri Natalia; Rahmayani, Anggita Amaliyah; Arta , Aryon; Nugroho , Rio; Sinta, Laras; Singo , Lloyd Shodiq (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Indonesia, as an archipelagic country with substantial fishery potential, faces challenges related to low fish consumption levels among its population. Muntai Barat Village in Bantan District, Bengkalis Regency, Riau Province, possesses significant fishery resources that remain underutilized. In response, a community service initiative comprising Fish Consumption Promotion Counseling and Fishery Product Demonstration was conducted to enhance public understanding of the importance of fish consumption and its health benefits, and to stimulate entrepreneurship and the creative economy by leveraging local fishery potential. The methods employed included interactive counseling and demonstrations of processed fish products, specifically mackerel and shrimp dumplings. Participants included 15 members of the village's women's group (PKK). The results indicated a significant increase in participants' knowledge of the nutritional content and benefits of fish, with a 45.34% improvement in post-test scores compared to pre-test results. All participants (100%) successfully created fish dumpling products, reflecting improved skills in processing fish into economically valuable products. Support from the village government in the form of business fund access for participants is expected to encourage the establishment of 3-5 fishery-based business units within six months. In conclusion, this activity effectively increased community awareness and skills in utilizing local fishery resources, potentially fostering the growth of the creative economy in the village.